2022
DOI: 10.1093/narcan/zcac034
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer resistance leads to a global deregulation of translation factors and unconventional translation

Abstract: Emerging evidence associates translation factors and regulators to tumorigenesis. However, our understanding of translational changes in cancer resistance is still limited. Here, we generated an enzalutamide-resistant prostate cancer (PCa) model, which recapitulated key features of clinical enzalutamide-resistant PCa. Using this model and poly(ribo)some profiling, we investigated global translation changes that occur during acquisition of PCa resistance. We found that enzalutamide-resistant cells exhibit an ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 142 publications
1
2
0
Order By: Relevance
“…These findings align with previous studies indicating that alterations in calcium regulation and vesicle trafficking can promote the growth and metastasis of PCa [42][43][44]. Second, scTIGER detected AR-regulated genes associated with changes in the initiation steps of translation, resulting in an overall decrease in mRNA translation in PCa [45,46]. Specifically, scTIGER identified AR downregulating NSUN6 expression in PCa, and it has been shown that mRNAs associated with NSUN6 exhibit higher rates of translation, thus causing a decrease in overall translation [47].…”
Section: Comparing Sctiger Performance With Other Methodssupporting
confidence: 91%
“…These findings align with previous studies indicating that alterations in calcium regulation and vesicle trafficking can promote the growth and metastasis of PCa [42][43][44]. Second, scTIGER detected AR-regulated genes associated with changes in the initiation steps of translation, resulting in an overall decrease in mRNA translation in PCa [45,46]. Specifically, scTIGER identified AR downregulating NSUN6 expression in PCa, and it has been shown that mRNAs associated with NSUN6 exhibit higher rates of translation, thus causing a decrease in overall translation [47].…”
Section: Comparing Sctiger Performance With Other Methodssupporting
confidence: 91%
“…Isolation of polysomal associated RNAs and polysomal profiles analysis were performed like previously described [ 38 ]. Briefly, livers from male Gulo −/− mice treated with 0% or 0.4% ascorbate were homogenized on ice by 10 strokes in an ice-cold Dounce homogenizer with 2 ml of lysis buffer (20 mM Tris, pH 7.4, 150 mM NaCl, 5 mM MgCl2, 40 U/mL Rnasin, 50 µg/mL cycloheximide, cOmplete™ EDTA-free Protease Inhibitor Cocktail (Roche, Indianapolis, IN, USA) and 1 mM dithiothreitol), and Nonidet P-40 substitute and sodium deoxycholate was added to a final concentration of 1% for lysis.…”
Section: Methodsmentioning
confidence: 99%
“…area corresponding to peaks of the 40 S, 60 S and 80 S ribosomal sub-units) and for polysomal fractions (i.e. area from the first polysomal peak to the twelfth polysomal peak, as reported [ 38 ]). The values for the lower limit of the Y axis were defined by the lowest points on each graph.…”
Section: Methodsmentioning
confidence: 99%